Western world - Salter, Christopher L. (Holt McDougal, Houghton Mifflin Harcourt, 2012)
Introduction to geography. A geographer's world ; Planet Earth ; Climate, environment, and resources ; The world's people -- The Americas. Early history of the Americas, 500 BC-AD 1537 ; Mexico ; Central America and the Caribbean ; Caribbean South America ; Atlantic South America ; Pacific South America ; The United States ; Canada -- Europe and Russia. Early history of Europe, 2000 BC-AD 1500 ; History of early modern Europe, 1500-1900 ; Modern European history, 1900-today ; Southern Europe ; West-central Europe ; Northern Europe ; Eastern Europe ; Russia and the Caucasus.